2014
DOI: 10.1002/jctb.4401
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid‐based three phase partitioning (ILTPP) systems for whey protein recovery: ionic liquid selection

Abstract: BACKGROUND The ionic liquid three phase partitioning (ILTPP) technique is a promising alternative to conventional processing technologies for protein separation and purification since it allows protein recovery at the liquid–liquid interface. In previous work, ILTPP has been developed with the BmimBF4/NaH2PO4 system for lactoferrin recovery, a bovine whey protein with important nutraceutical properties. However, BmimBF4 may suffer from hydrolysis when it is in contact with water, so the selection of an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
(101 reference statements)
0
31
1
Order By: Relevance
“…Alvarez‐Guerra and Irabien suggested that the salt concentration has the greatest influence on the amount of lactoferrin recovered at the interface. However, pH, temperature and protein concentration also influence the partitioning …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alvarez‐Guerra and Irabien suggested that the salt concentration has the greatest influence on the amount of lactoferrin recovered at the interface. However, pH, temperature and protein concentration also influence the partitioning …”
Section: Resultsmentioning
confidence: 99%
“…However, pH, temperature and protein concentration also influence the partitioning. 52 The three systems studied in the current research were used previously for the partitioning of different proteins, including Rubisco. 14,29,35 No precipitation of these proteins was reported, demonstrating that the studied systems do not always form three phases.…”
Section: Protein Partitioning In Atpssmentioning
confidence: 99%
“…The formation of an interface of precipitated proteins in these ABS could be a potential strategy to purify IgG from complex matrices within a three‐phase partitioning (TPP) approach, where the target compound is enriched at the interface of two liquid phases . The t ‐butanol and ammonium sulfate aqueous solutions are often used to induce the precipitation of biomolecules at the interface, and recently, Alvarez et al . showed that this approach is also feasible with ILs – ionic‐liquid‐based three‐phase partitioning (ILTPP).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, in this section, we have tried together all these research reports under the same roof, so that it is easily available to the readers and also to expose its importance to the scientific world. An overview of the literature reveals stability studies of proteins such as amyloglucosidase [79], thyroglobulin [79], glutamate dehydrogenase [79], lactate dehydrogenase [79], glucose dehydrogenase [80], formate dehydrogenase [94], glycosidase (α and β) [81], monellin [82], β-galactosidase [83], glucose oxidase [106], lactate oxidase [109], oxidoreductases [107], subtilisin Carlsberg [84], Amano protease P6 [85], pepsin [86], papain [87,100] esterases from Bacillus subtilis and Bacillus stearothermophilus [87], Penicillium expansum lipase [88], mushroom tyrosinase [88], chloroperoxidase [89], porcine pancreatic lipase [91], α-helical protein Im7 [92], pepsin [93], adenosine deaminase [95], α-amylases [96], xylanase II (GH11 enzyme, from Trichoderma longibrachiatum [97], lactoferrin [99], α-synuclein [101,103], ribonuclease A [102], casein [104,105], epoxide hydrolase [110], avidin [111], Abeta peptide [112], zein [113] and firefly luciferase (Photinus pyralis luciferase) in the ILs. Among them some of the proteins have been stabilized [79]…”
Section: Structure and Stability Of Some Other Proteins In Different Ilsmentioning
confidence: 99%